HYBRID-CMOS LOGIC STYLE DESIGN FOR FAST SELF-CHECKING ADDERS DATA PATHS (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper we present an efficient design for self-checking fast adders data paths. We investigate the implementation of concurrent error detection fast adders: carry look-ahead, Carry skip, Carry-select and Conditional-Sum adders. To achieve a low overhead, low power design, we use hybrid-CMOS logic style and combine Conventional CMOS and CMOS Pass transistor Logic (CPL). The proposed schemes are Totally Self-Checking (TSC). They are fully differential and checked by dual-rail and parity codes.